2020
DOI: 10.32474/osmoaj.2020.03.000171
|View full text |Cite
|
Sign up to set email alerts
|

Statements Concerning the Patellofemoral Joint

Abstract: This is different statements in respect to understanding and treating patients having patellofemoral problems. The statements are based upon scientific data and clinical experience and they reflect the authors opinion. The statements are specifically selected in relation to specific topics with little consensus and/or frequent misunderstandings. Subjects like first time patella dislocations, trochlea anatomy, tibia tubercle trochlea groove distance (TTTG), patella alta, medial patellofemoral ligament reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…That abnormal trochlea offers inadequate patellar tracking during flexion and leads to subluxation or dislocation of the patella and eventually can cause PC. 46 , 47 , 48 , 49 , 50 Multiple studies, together with trochlear dysplasia, have also discovered a supratrochlear spur, also called trochlear bump/lump, which is a prominent, dysplastic beginning of the lateral femoral condyle visible in lateral x-rays, consistent with the Dejour classification of trochlear dysplasia. 9 Beaufils et al.…”
Section: Discussionmentioning
confidence: 61%
“…That abnormal trochlea offers inadequate patellar tracking during flexion and leads to subluxation or dislocation of the patella and eventually can cause PC. 46 , 47 , 48 , 49 , 50 Multiple studies, together with trochlear dysplasia, have also discovered a supratrochlear spur, also called trochlear bump/lump, which is a prominent, dysplastic beginning of the lateral femoral condyle visible in lateral x-rays, consistent with the Dejour classification of trochlear dysplasia. 9 Beaufils et al.…”
Section: Discussionmentioning
confidence: 61%
“…Balcarek et al 2 observed that LTI angle decreased at higher grades of TD evaluated by the Dejour classification. We did not include the commonly used Dejour classification in this study given its low reproducibility 7 and its subjectivity. Further, a biomechanical study by Van Haver et al 41 did not demonstrate any significant differences between the 4 Dejour types with respect to instability.…”
Section: Discussionmentioning
confidence: 99%